1971
DOI: 10.1136/bmj.3.5768.236
|View full text |Cite
|
Sign up to set email alerts
|

Research into psoriasis--the last decade.

Abstract: Psoriasis is an infuriating disease. It is an arrogantly trivial disorder placqued on to a systemically unimportant organ. Yet it affects 1-2% of the population,62 some of whom are so badly afflicted that life is reduced to a biological chore. This is the frustration: the psoriatic without his spots is totally fit. So that, in terms of personal happiness and social usefulness, research into psoriasis has more to achieve than many of the spectacular endeavours of contemporary medical science. All of us Increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

1973
1973
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 87 publications
0
7
0
1
Order By: Relevance
“…8 Moreover, a number of epidermal dermatoses, ranging from occupational dermatitis to psoriasis, may be triggered by extended injury to the epidermis. 17,18 Furthermore, we previously reported that prolonged barrier disruption, produced by repeated topical acetone treatment or tape stripping, induced epidermal hyperplasia, cytokine secretion and inflammation. 12 As certain clinical disorders, in which barrier function is abnormal, are also characterized by epidermal hyperproliferation and cutaneous inflammation, the decline in barrier homeostasis might induce these skin disorders.…”
Section: Discussionmentioning
confidence: 96%
“…8 Moreover, a number of epidermal dermatoses, ranging from occupational dermatitis to psoriasis, may be triggered by extended injury to the epidermis. 17,18 Furthermore, we previously reported that prolonged barrier disruption, produced by repeated topical acetone treatment or tape stripping, induced epidermal hyperplasia, cytokine secretion and inflammation. 12 As certain clinical disorders, in which barrier function is abnormal, are also characterized by epidermal hyperproliferation and cutaneous inflammation, the decline in barrier homeostasis might induce these skin disorders.…”
Section: Discussionmentioning
confidence: 96%
“…1 In the past, the disease was thought to originate from a primary disorder in epidermal keratinocytes that led to their hyperproliferation and incomplete maturation. [2][3][4] Leukocyte infiltration was only viewed as a secondary event. However, the implication of the immune system as an initiator of the symptoms in psoriasis was slowly recognized in the 1980s when new evidences, such as successful treatment with cyclosporin A, a T-cell immunosuppressant, demonstrated the necessity of immune cells in the development of lesions.…”
mentioning
confidence: 99%
“…Further investigations in the 1970s revealed the role of immunologic factors in psoriasis. However, the dominant thought was that psoriasis was a disease of faulty epidermopoiesis due to impaired autocontrol mechanisms [12]. Hunter et al wrote "More work on cell turnover and its regulation will give the clue to psoriasis" [13].…”
Section: Pre-biologic Immunological History Of Psoriasismentioning
confidence: 99%